ANÁLISIS DE LA CALIDAD DE SERVICIOS, QUE PRESTA LA OPERADORA TURÍSTICA TRAVESÍAS DEL SUR, DE LA CIUDAD DE LOJA - OCHOA ALEJANDRO, KAREN LEONOR (2019)
The purpose of this thesis is to evaluate the quality of the service provided by the Tour Operator “Travesias del Sur”, since today what people are looking for is quality in what they receive, that is, an excellent service. IN THE FIRST OBJECTIVE: to diagnose the current situation of the Tour Operator “Travesías del Sur”, the current situation of the company is described by means of an own elaboration matrix to gather the information required by it. An interview was directed to the manager and another interview to the sales agent of the tour operator to then determine to perform a SWOT matrix that allowed identifying the Strengths and Weaknesses of the same; advantageous information for planning strategies to improve the service provided by the operator. IN THE SECOND OBJECTIVE: To evaluate the quality of the service offered by the Tour Operator “Travesías del Sur”, for the fulfillment of this objective, a survey based on the SERVQUAL Model was designed to determine the virtues and weaknesses that clients of Travesías del Sur find in the service it offers. A SWOT matrix was developed that allowed to know the Operator's Opportunities and Threats through the results obtained from the applied surveys. IN THE THIRD OBJECTIVE: To propose strategies for the improvement of the quality of the service of the Tour Operator “Travesías del Sur”, here we have proposed improvement strategies so that the company provides a better service to its clients and can feel fully satisfied, since It is intended to meet all your needs. In conclusion of the objectives set forth in the present investigation, they were met according to what was established, that is to say that the tour operator Travesías del Sur complies with regard to permits, activities and requirements for its proper functioning; It should be noted that although it complies with everything established in the parent company, it does not have enough personnel to cover the areas that make up the company, so there is no good customer service. On the other hand, through direct observation, it was appreciated that it does not have a uniform, which does not allow a good corporate image to distinguish between the other agencies. It is also proposed to implement a service qualifier that allows measuring customer satisfaction at the time of receiving the service so that the owner can be aware of the service provided. That is why it is important that the